Teaching a stone to talk eaudiobook Expeditions and encounters. - Dillard, Annie (Tantor Audio, 2016)
In this dazzling collection, Annie Dillard explores the world over, from the Arctic to the Ecuadorian jungle, from the Galapagos to her beloved Tinker Creek. With her entrancing gaze she captures the wonders of natural facts and human meanings: watching a sublime lunar eclipse, locking eyes with a wild weasel, or beholding mirages appearing over Puget Sound through summer. Annie Dillard is one of the most respected and influential figures in contemporary nonfiction and winner of the Pulitzer Prize. Teaching a Stone to Talk illuminates the world around us and showcases Dillard in all her enigmatic genius.